KASIH KARUNIA SEBAGAI DASAR ETIKA KEHIDUPAN KRISTEN DALAM PANDANGAN JOHN CALVIN - Jendy Megumi Ponggohong; Riedel Christian Gosal (STT-RAI Batam, 2026)
This article examines John Calvin's thought on grace (gratia Dei) as the foundational principle of ethics in Christian life. According to Calvin, fallen humans are inherently incapable of performing truly good actions without the intervention of God’s grace; thus, all genuine moral acts arise from hearts renewed by the Holy Spirit. The study was conducted in three main stages. First, conceptual observation of modern moral phenomena, highlighting the tendency of humans to place themselves at the center of morality, apart from God’s authority, resulting in ethical relativism. Second, a literature review covering both classical and contemporary works, including Calvin’s writings, as well as research from the past five years on the relationship between grace and Christian ethics. Third, a descriptive-theological analysis of the collected data to interpret and integrate Calvin’s perspective on grace and ethics. The findings indicate that Christian ethics, according to Calvin, does not exist independently as a moral system but is the fruit of God’s grace, guiding believers to live holy, responsible lives that reflect Christ in all aspects of personal, social, and church community life. This article emphasizes the continued relevance of Calvin’s teaching for the contemporary church, especially in confronting moral challenges, ethical relativism, and modern cultural pressures that often prioritize human autonomy.